(untitled) (Research, Society and Development, 2022)
Objective: To analyze the practice of physical activity and its influence on the quality of life of prison officers. Method: Research carried out with prison officers in the city of Jequié/Ba. The reporting of demographic data through the bioelaborated by the investigation. To test the level of physical activity and quality of life from the IPAQ and quality of life from the WHOQOL-bref. Data were tabulated and analyzed using SPSS version 210. As categorical variables through frequencies and as intervals through measures of central tendency and dispersion, 95% confidence was used (p<0.05). Results: The mean age was 44 years (±8), a prevalence of sedentary behavior of 63.3% (n=62). Among men with sedentary behavior, males (77.4%), non-whites (83.9%), with partners 61.3%) and with higher education (51.6%) prevailed. The quality of life or lower domain was environmental for the groups, with a median of 60.9% and 59.4%, respectively. Conclusion: It is necessary to develop proposals for interventions in the work environment of penitentiary agents and to encourage physical activity to improve health conditions, lifestyle and consequently the quality of life of these workers.